CHILDREN’S DIRECT AND INDIRECT EXPERIENCES WITH NATURE AND THEIR CONNECTEDNESS TO NATURE - Mustapa, Nor Diyana; Maliki, Nor Zarifah; Aziz, Nor Fadzila; Hamzah, Aswati (PLANNING MALAYSIA, 2019)
Direct experiences with nature during childhood plays an important role to influence children’s connectedness to nature (CTN) as a child now and later as an adult. However, today’s children obtain nature experiences mostly through indirect ways (e.g. observing nature and vicarious learning), which may not have the same quality as direct ways (e.g. activities with plants and earth elements). Hence, this study aims to first identify the current trends of children experience nature and further examine the effects of both direct and indirect experiences with nature on their CTN. Questionnaires were distributed to 760 children from 20 schools include both urban and rural schools in Kedah and Penang, Malaysia. The data were analysed using mean score, standard deviation, and multiple regression. The results confirmed that the current trends of children having experiences with nature are more through indirect ways. Results also showed that indirect experiences with nature make more contribution to children’s CTN than direct experiences. Overall, this study highlights that indirect experiences with nature can be an alternative and effective way to develop children’s CTN without neglecting the importance of direct experiences with nature.